Analysis of Factors Affecting Beef Cattle Business Income (Case in Cipari Village, Cigugur District, Kuningan Regency) - Mahdi Sumaryanto, Iftikhor; Azril Fadhila, Reynaldi; Fahri Gibran, Muhamad; Aisyah, Siti; Faqih, Achmad (Devotion : Journal of Research and Community Service, 2024)
The purpose of this study is to find out the factors that affect the income of beef cattle business in Cipari Village, Cigugur District, Kuningan Regency. This research was carried out at the Beef Cattle Farm Owned by Cipari Village, Kalibaru Village, Cigugur District, Kuningan Regency, West Java Province. The time of this research will be carried out in May - July 2024. The method in this study uses a quantitative descriptive method with a survey approach. The sampling technique in this study is to use saturated sampling (census). The sample in this study is all cattle breeders in Cipari Village consisting of 17 farmers with the ownership of 2 to 4 beef cattle. The Data Analysis Techniques carried out in this study include descriptive analysis quantitative, i.e. Multiple linear regression analysis. The results of the study show that (1) The number of beef cattle, the selling price of livestock, the labor cost factor, the price of beef cattle, the feed price factor, and the price of medicines, simultaneously have a significant effect on the income of the beef cattle business in Cipari Village, Cigugur District, Kuningan Regency; (2) The most influential factor on the income of the beef cattle business is the Number of Beef Cow Factor, because the number of beef cattle has the most significant influence on income.